Situational Leadership Style Its Influence On Employee Performance: Work Environment As A Mediation Variable - Adi Syahdana Nurfauzi; Barin Barlian; Ghaling Achmad Abdul Ghonisyah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research purposse to determine and analyze (1) Description of Situational Leadership Style, Work Environment and Performance of Production Operator Employees at PT. Rentang Buana Niaga Makmur Tasikmalaya. (2) The Influence of Situational Leadership Style on the Performance of Production Operator Employees at PT. Range Buana Niaga Makmur Tasikmalaya. (3) The Influence of Situational Leadership Style on the Work Environment of Production Operator Employees at PT. Range Buana Niaga Makmur Tasikmalaya. (4) The Influence of the Work Environment on the Performance of Production Operator Employees at PT. Rentang Buana Niaga Makmur Tasikmalay and (5) The Influence of Situational Leadership Style Through the Work Environment on the Performance of Production Operator Employees at PT. Rentang Buana Niaga Makmur Tasikmalaya.. The method used in this research is a survey. With a research sample of 45 production operator employees as respondents. The data used is primary and secondary data. The analytical tool used in this research is path regression analysis using the SPSS version.25 support application and the Sobel Test. The results of the research show that the implementation of the Situational Leadership Style at PT Rentang Buana Niaga Makmur Tasikmalaya has been carried out well. The work environment at PT Rentang Buana Niaga Makmur Tasikmalaya is also in the good category and employee performance at PT Rentang Buana Niaga Makmur Tasikmalaya is in the high category. Situational Leadership Style has a significant effect on employee performance variables. Situational Leadership Style has a significant effect on work environment variables. The work environment has a significant effect on employee performance. There is an indirect influence between Situational Leadership Style on employee performance through the work environment.